The Use of Person-Centered Approach for Controlling the Anxiety of the Athletes - Patsiaouras Αστέριος; Soulas ∆ηµήτρης; Papanikolaou Ζήσης (Inquiries in Physical Education and Sport, 2003)
The purpose of this study was to investigate the effect of the selected principles, methods and strategies of the person-centered approach (genuineness, warmth, empathy) on controlling the anxiety in track and field athletes. The subjects involved in this study were four male and four female track and field athletes. The intervention program that used was a modified person-centered approach, combining selected aspects of Rogerian extended person-centered psychotherapy. Pre- and post- tests with Mental Readiness Form (MRF) were used to measure the effect of the person-centered approach in the level of anxiety and self-confidence of the athletes. Statistical differences were observed for trait anxiety (p= .047) and self-confidence (p=.035) between the pre- and the post- test. Non significant results were observed for the factor of state anxiety. It seems that the person-centered approach did reduce the trait anxiety among the athletes and their self–confidence. Future research must also investigate the psychological phenomena of negative feelings, aggressiveness and motivation in sports.